Multicultural teaching competence among preservice teachers in Ghana: the role of critical self-reflection, religious inclusivity, and teaching self-efficacy - Eric Mensah; Martin Owusu; Ernest Nyamekye (Discover Education)
Abstract This study investigated the multicultural teaching competence (MTC) of preservice teachers and the predictors of their competence. It ultimately investigated how preservice teachers' sense of efficacy (TSE), critical self-reflection (CSR), and religious inclusivity (RI) predicted their MTC. Through a cross-sectional research design, data were drawn from 146 preservice religious and moral education and Ghanaian language and cultural education preservice teachers in a Ghanaian university. Descriptive statistics and partial least squares structural equation modelling analysis were employed. The descriptive results indicate that preservice teachers possess a moderate level of MTC, RI, TSE, and CSR. The structural equation modelling results revealed that RI, TSE, and CSR have a significant positive influence on teachers' MTC. Further analysis showed that RI significantly mediates the influence of CSR on the MTC of preservice teachers. Self-efficacy was also found to mediate the relationship between CSR and MTC. Based on these statistical insights, constructive recommendations to improve educational policy and practice have been offered for consideration.